Neurovascular surgery - Carter, L. Philip; Spetzler, Robert F.; Hamilton, Mark G. (McGraw Hill, 1994)
This illustrated work includes all neurovascular operative procedures. In addition to step-by-step depiction of each surgical technique, clinical and radiologic diagnostic procedures as well as comprehensive pre- and post-operative care is included. Coverage begins with a review of basic anatomy, physiology and cerebral blood flow followed by hemorrhagic cerebral vascular disease, neurovascular compression abnormalities, spinal injuries and traumatic vascular injury.